SIM and the City: Rationalism in Psychology and Philosophy and Haidt's Account of Moral Judgment - Clarke, S (2008)
Jonathan Haidt (2001) advances the 'Social Intuitionist' account of moral judgment, which he presents as an alternative to rationalist accounts of moral judgment, hitherto dominant in psychology. Here I consider Haidt's anti-rationalism and the debate that it has provoked in moral psychology, as well as some anti-rationalist philosophical claims that Haidt and others have grounded in the empirical work of Haidt and his collaborators. I will argue that although the case for anti-rationalism in moral psychology based on the work of Haidt and his collaborators is plausible, a decisive case has yet to be made. It will require further experimental evidence before a decisive case could be made. My assessment of anti-rationalist philosophical arguments that are grounded in the empirical work of Haidt and his collaborators is much more negative than this. I will argue that this body of empirical work is a very unpromising basis for such arguments.